1986
DOI: 10.1037/0022-3514.50.3.523
|View full text |Cite
|
Sign up to set email alerts
|

Social status in small groups: Individual–group similarity and the social "misfit."

Abstract: Research on social development often attempts to predict social status in children's peer groups using personality features or traits of the individual child. Yet few personality measures consistently predict social acceptance across different groups, and those predictors that are consistent generally account for small proportions of the variance in status. This article proposes that social status is a function of both individual and group characteristics. It is argued that two factors are necessary to predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
389
4
28

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(463 citation statements)
references
References 39 publications
37
389
4
28
Order By: Relevance
“…We suggested that numerical majority group victims resemble social misfits (Wright et al 1986) who deviate from what is perceived as normative for their group. Residing in nondiverse classrooms with many same ethnicity peers, these youth are more susceptible to causal interpretations of non-normative behavior that implicate the self (''it must be me'').…”
Section: Self-blame and The Ethnic Diversity Contextmentioning
confidence: 95%
See 1 more Smart Citation
“…We suggested that numerical majority group victims resemble social misfits (Wright et al 1986) who deviate from what is perceived as normative for their group. Residing in nondiverse classrooms with many same ethnicity peers, these youth are more susceptible to causal interpretations of non-normative behavior that implicate the self (''it must be me'').…”
Section: Self-blame and The Ethnic Diversity Contextmentioning
confidence: 95%
“…Being a victim when one's ethnic group is numerically more powerful might be especially debilitating because that individual deviates from what is perceived as normative for their group (i.e., to be dominant). Social psychologists have used the term social misfit to describe the negative outcomes of an individual whose problem social behavior deviates from group norms (Wright et al 1986). …”
Section: Ethnicity As a Context For Peer Victimizationmentioning
confidence: 99%
“…Peer influence may be particularly hazardous for children attending urban schools where a high density of aggressive behavior makes classroom management difficult and encourages normative beliefs that support aggression (Boivin, Dodge. & Coie, 1995;Wright et al, 1986). Programs designed to reduce aggression in the school are warranted, including attempts to improve student conflict resolution skills and improve teacher skills at managing problem behavior in the classroom (Weissberg & Greenberg, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…That is, school-based behavior problems appear fostered by classrooms that contain many aggressive children, perhaps because aggressive behavior is more likely to be viewed as acceptable by peers (Wright, Giammarino, & Parad, 1986), teachers are more likely to find it difficult to manage aggression effectively and suppress it consistently (WerthamerLarson, Kellam, & Wheeler, 1991), and peers are more likely to react to aggression with escalating negative chains of counteraggression (Asarnow, 1983;Cairns et al, 1989). Although rural school districts face some disadvantages when compared to urban districts, such as lower per-pupil school expenditures, a narrower curriculum, and more poorly paid and less welltrained teachers (Sherman, 1992), they are at an advantage in terms of school characteristics associated with child aggression.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate a link between being bullied and being perceived by the peers as different or deviant, which in turn could be understood from the perspective of the stigma theory (Goffman 1963;Jones et al 1984), the labelling theory (Becker 1963) and the social misfit hypothesis (Wright, Giammarino, and Parad 1986), which all claim that identifying and defining a peer as deviant is always a social construction produced in the peer group associated with its culture and social norms. When a student is labelled as deviant, other peers interpret him or her as a person who violates important social taken-for-granted norms or normative standards of the peer culture.…”
mentioning
confidence: 99%